KONSEP “LÈBUR ÈABES” PADA PENATAAN TATA LETAK TOKO KELONTONG MADURA: “LÈBUR ÈABES” CONCEPT IN MADURA GROCERY STORE LAYOUT - Ardan Dikri Purnama; Krishna Hutama; Yan Yan Sunarya (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2026)
“Lèbur Èabes” Concept In Madura Grocery Store Layout. Toko kelontong Madura reflect a a unique blend of local cultural values and adaptive design principles. This study explores how the concept of "lèbur èabes" embodies the hard work and adaptability of the Madurese community in the layout and design of toko kelontong. By utilizing a design approach based on the principles of balance, contrast, and unity, toko kelontong Madura successfully create an aesthetic and functional spatial arrangement that offers a comfortable shopping experience. The methodology of this study includes collecting and classifying data related to cultural context and toko kelontong, analyzing and interpreting structural elements, and describing the integration of the "lèbur èabes" concept with design principles. The findings reveal that the "lèbur èabes" concept will continue to transform over time. The transformation occurring in toko kelontong Madura results from an iterative design process that combines traditional values with the needs of urban consumers.